2019
DOI: 10.3390/su11123331
|View full text |Cite
|
Sign up to set email alerts
|

Regional Sustainability, Individual Expectations and Work Motivation: A Multilevel Analysis

Abstract: In the context of the recent labor shortages in Eastern European countries, Romania included, companies, organizations and decision makers need to strongly address the issue of labor motivation for increasing worker performance and also for attracting the scarce labor resources. The main goal of the research is to explore new determinants of work motivation, such as regional sustainability and also individual factors related to individual expectations. Therefore, the responsive methodology used for this purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
(28 reference statements)
2
9
0
Order By: Relevance
“…The occupational and educational choices of young people depend on many different factors related to both individual characteristics of these people including their work motivation (Davidescu, Roman, Strat and Mosora, 2019) as well as the socioeconomic situation of a country. This work focuses on this first group of factors except for work motivation, due to the lack of relevant data for Poland in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The occupational and educational choices of young people depend on many different factors related to both individual characteristics of these people including their work motivation (Davidescu, Roman, Strat and Mosora, 2019) as well as the socioeconomic situation of a country. This work focuses on this first group of factors except for work motivation, due to the lack of relevant data for Poland in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to bear in mind that not all sustainable HRM practices will necessarily yield the same effect on employees and/or organizations. For example, Davidescu, Roman, Strat, and Mosora's (2019, p. 1) study of regional sustainability, individual expectations, and work motivation in the Romanian context found that “social sustainability has a significant impact on work motivation,” but economic and environmental sustainability “have no significant impact on work motivation.”…”
Section: Future Research Agendamentioning
confidence: 99%
“…Life satisfaction is a mental construct that evaluates well-being of life in general [59]. Several scholars have investigated this relationship and found it to be directly propor between life and job satisfaction [14,60,61].…”
Section: Determining Factors For Job Satisfaction and Research Hypoth...mentioning
confidence: 99%